2022
DOI: 10.1093/plcell/koac086
|View full text |Cite
|
Sign up to set email alerts
|

Systems approaches reveal that ABCB and PIN proteins mediate co-dependent auxin efflux

Abstract: Members of the B family of membrane-bound ATP-binding cassette (ABC) transporters represent key components of the auxin-efflux machinery in plants. Over the last two decades experimental studies have shown that modifying ABCB expression affects auxin distribution and plant phenotypes. However, precisely how ABCB proteins transport auxin in conjunction with the more widely studied family of PIN-formed (PIN) auxin efflux transporters is unclear, and studies using heterologous systems have produced conflicting re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 73 publications
2
24
0
Order By: Relevance
“…The main differences between these alternatives lie in the geometrical representation of individual cells and the way physical and chemical interactions among cells are handled (Band et al, 2012a). Early multicellular models used a structured rectangular grid to depict root topologies (Grieneisen et al, 2007; Mähönen et al, 2014; Mironova et al, 2012), however, recent models use realistic root anatomies, derived either from digitised microscopic images (Band et al, 2012a; Mellor et al, 2016, 2022; Moore et al, 2015, 2017) or idealised using computational tools (Di Mambro et al, 2017). Different frameworks to develop multicellular models exist, namely CellModeller (Dupuy et al, 2008, 2010), OpenAlea (Collis et al, 2022; Pradal et al, 2008), VirtualPlantTissue (De Vos et al, 2017; Merks et al, 2011) and MECHA (Couvreur et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The main differences between these alternatives lie in the geometrical representation of individual cells and the way physical and chemical interactions among cells are handled (Band et al, 2012a). Early multicellular models used a structured rectangular grid to depict root topologies (Grieneisen et al, 2007; Mähönen et al, 2014; Mironova et al, 2012), however, recent models use realistic root anatomies, derived either from digitised microscopic images (Band et al, 2012a; Mellor et al, 2016, 2022; Moore et al, 2015, 2017) or idealised using computational tools (Di Mambro et al, 2017). Different frameworks to develop multicellular models exist, namely CellModeller (Dupuy et al, 2008, 2010), OpenAlea (Collis et al, 2022; Pradal et al, 2008), VirtualPlantTissue (De Vos et al, 2017; Merks et al, 2011) and MECHA (Couvreur et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…ABCB19 co-localizes and stabilizes PIN1 in membrane lipid microdomains to enhance PIN1 transport activity (Titapiwatanakun et al 2009). Computational modelling further supports the synergistic interactions of ABCB and PIN proteins for directional auxin ow (Mellor et al 2022). Beside of auxin export system, auxin uptake is also an active process which requires proton motive force.…”
Section: Auxin Transportmentioning
confidence: 70%
“…Genetic and biochemical studies have indicated a tight interplay between both PINs and ABCBs (Bandyopadhyay et al, 2007;Blakeslee et al, 2007;Mravec et al, 2008;Deslauriers & Spalding, 2021). A recent simulation of auxin transport in the root meristem identified strong PIN-ABCB co-dependent auxin efflux, in combination with individual auxin transport activities, and fluxes via plasmodesmata as the most likely scenario underpinning auxin transport in the root tip (Mellor et al, 2020(Mellor et al, , 2022. The proposed auxin transport components of the reverse fountain are AUX1, for auxin uptake, in combination with PIN1, PIN2, PIN3, PIN4, PIN7, ABCB1, ABCB19, and ABCB4 for auxin efflux.…”
Section: Introductionmentioning
confidence: 99%